An Error Analysis of Active and Passive Voice Towards English Text of University Students in South Jakarta - Irfan Hadi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is aimed at analyzing univeristy students’ errors in using Passive Voice. Specifically, it is aimed for obtaining and identifying the common error in using passive voice and finding out what factors which trigger the students make such errors. The data sources of this research were 38 students of fifth semester university students of in South Jakarta which were taken by random sampling. The researcher used the descriptive analysis method in this research to describe students’ errors and analyzed the data by using formula: P = The data were taken from the test. The findings showed that there are 229 errors made by students. The common error made by students in using Passive Voice was Misformation, which consists of 152 errors or 66.3%. According to Brown’s theory, it was interpreted that, intralingual transfer, interlingual transfer, context of learning and communicative strategies are causes of those errors.